The possibilities of applying blockchain technology in shipping - Jugović, Alen (Array, 2019)
Blockchain technology is a decentralized database which stores the registry of property and transactions using a peer-to-peer network, secured by cryptography, and over time, its history is locked into blocks of data which are cryptographically connected and secured. The blockchain technology was primarily designed for application in cryptocurrency transactions and related digital agreements. Due to its immutable and infallible record of all transactions within the network, the potential of this technology for broad application has been recognized. This paper analyzes the possible advantages of applying blockchain technology in logistics and maritime transport.